Pengembangan Buku Ajar Bahasa Inggris untuk Peserta Didik Lamban Belajar - Nurhayati, Titis; Rufi'i, Rufi'i (JOEAI (Journal of Education and Instruction), 2020)
This research aims to develop English teaching books for students who are slow to learn grade VII SMP Negeri 29 Surabaya. This development research refers to the development design measures developed by Dick & Carey. The development design is grouped into four development procedures, namely data analysis stage, product design stage, validation and evaluation stage and final production stage. Product trials conducted by material experts and design experts, as well as field tests conducted on 8 students slow to learn grade VII. Data collection using interview guidelines, observations, questionnaires for material experts, questionnaires for design experts, student response questionnaires, and test script instruments. The results of the study, from data analysis, the validation results of content experts obtained a value of 98%, from design experts obtained a value of 80%, and field tests got a score of 92%. In conclusion, the development of English teaching books for students who are slow to learn meets the criteria is very feasible to be used in learning activities, and can improve the learning outcomes of learners sluggish learning, this can be seen from the results of the training and the attitude of students to English teaching materials. Keywords: Textbooks, English, Sluggish learning, Development